Characterization of mandarin citrus germplasm from Southern Brazil by morphological and molecular analyses - Santos, Patrícia Koehler; Dornelles, Ana Lúcia Cunha; Freitas, Loreta Brandão de (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to characterize mandarin (Citrus spp.) germplasm from Southern Brazil by morphological and molecular analyses. Thirty seven cultivars from 34 distinct mandarin varieties were evaluated by morphological and agronomic traits of leaves, flowers and fruits, and by microsatellite markers. The morphological and agronomic characteristics suggested that almost all varieties can be produced for commercial use, and some, as the Satsuma variety, are recommended for breeding programs. Pooled DNA samples from 1-5 plants belonging to each cultivar were tested. Eight of the nine primers detected polymorphisms. Specific markers were found for some accessions. The dendrogram constructed with the morphological results divided the 37 cultivars into four groups, while that obtained with the microsatellites clustered 35 of the 37 cultivars into three groups only. Generally, intervarietal differences are not high, and this lack of agreement in the two multifactorial analyses indicates that diverse evolutionary factors are acting at these two levels of investigation.